Measuring the Sustainable Development and Building Its Global Indicators: The Methodological Framework - Kobylynska, Т. V.; Kobylynskyi, V. M. (Statistics of Ukraine, 2024)
The article elaborates on the methodological framework for measurement of the sustainable development, incorporated in the EU policy and legislation through the strategy for socio-economic development of EU “Europe 2020”. The 2030 Agenda on Sustainable Development (referred to hereinafter as the 2030 Agenda), fully conforming to the EU’s vision of the future, has become a sustainable development blueprint at global scales. EU member states continue to be leaders in implementing the 2030 Agenda and SDGs with the full compliance with the subsidiarity principle. The monitoring on the progress on the way to SDGs is carried out by the SDGs nomenclature using open and inclusive approach, with the involvement of EU Council Committees (economics, financial, labor, social protection), the European Statistical Advisory Committee, the European Environment Agency, non-government organizations, other international organizations and research circles. The indicators measuring the progress towards SDGs have been selected in view of their compliance with the EU policy, potentials, accessibility, country coverage, timeliness and quality. It is emphasized in assessing the regional and sub-regional progress towards SDGs, the United Nations Economic and Social Commission for Asia and the Pacific (UNESCAP) uses two main indicators: index of current progress and index of achieved progress. Three main approaches designed for the same purpose, to assess the progress towards SDGs, were analyzed. It was revealed that these approaches provide responses on absolutely different questions. As each method is specific in terms of data set, analytical tools and ways of results’ interpretation, each country should make its own choice of the methodology to be used. The notion of “achieved progress” can have many different definitions depending on what dimension is addressed, what goal is set, what comparison is made, how the data are aggregated or how the indicators are selected and used. Regarding the domestic trends, it is highlighted that the national statistical system of Ukraine jointly with VoxUkraine and with support from the UN Development Program for Ukraine makes assessment of the progress towards SDGs by UNESCAP methodology.